Brea Souders - another online pervert - Souders, Brea 1978- (MACK, 2023)
"Another Online Pervert derives from a series of conversations between artist Brea Souders and a female online chatbot. These real-time conversations are interspersed with entries from Souders' diary spanning twenty years, unfolding with a surprising and improvisational quality in combination with photographs from Souders' archive. With this personal and provocative book, we are guided through a unique exploration of how a machine and a human can learn from one another and build a shared story from pieces of themselves.